1989
DOI: 10.1203/00006450-198907000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Plasma β-Casomorphin-7 Immunoreactive Peptide Increases after Milk Intake in Newborn but not in Adult Dogs

Abstract: ABSTRACT. To determine the relation between milk intake and plasma levels of P-casomorphins as a function of age, we studied the levels of P-casomorphin-7 immunoreactive material (BCMIR) in 2-and 4-wk-old beagle neonates and adult dogs following milk intake. We used three kinds of milk: 1) bovine casein-based milk formula; 2) canine bitch's milk, and 3) soy protein-based (noncasein) formula. Using a new extraction technique, BCMIR was isolated from plasma and assayed by radioimmunoassay at 0, 2, 4, and 6 h aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
3

Year Published

1993
1993
2010
2010

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 11 publications
1
18
0
3
Order By: Relevance
“…Carmine red GIT was signifi cantly higher in rats on hydrolyzed than [16][17][18][19][20] ; p = 0.6). Small bowel transit was also signifi cantly higher with hydrolyzed (78.8 8 7.0%, n = 8) compared to native casein (67.4 8 5.1%, n = 9; p !…”
Section: Resultsmentioning
confidence: 98%
“…Carmine red GIT was signifi cantly higher in rats on hydrolyzed than [16][17][18][19][20] ; p = 0.6). Small bowel transit was also signifi cantly higher with hydrolyzed (78.8 8 7.0%, n = 8) compared to native casein (67.4 8 5.1%, n = 9; p !…”
Section: Resultsmentioning
confidence: 98%
“…The possible physiological importance of opioid substances derived from milk proteins for the neonate [62] may be deduced from the existence of 8-casomorphin immunoreactive material in the plasma of newborn calves after their first bovine milk feeding [25] as well as in two weeks-old dogs after canine milk intake [63]. But casomorphins or precursor molecules of these opioid casein fragments have not been detected in plasma of newborn calves before milk feeding [63] or in adult humas [64].…”
Section: )mentioning
confidence: 98%
“…But casomorphins or precursor molecules of these opioid casein fragments have not been detected in plasma of newborn calves before milk feeding [63] or in adult humas [64]. Thus, in adult mammals casomorphins cannot enter the cardiovascular compartment, i.e.…”
Section: )mentioning
confidence: 98%
“…In vitro research revealed that gluten [20] and casein [21] have potentially opioid segments called gliadorphins [22] and beta-casomorphins [23], respectively. Intact transport of beta-casomorphins has been shown across intestinal The organic acid test is not validated; microbiologic confirmation of the overgrowth is necessary mucosa in the neonatal period in dogs [24]. Altered intestinal permeability has been described in children with autism.…”
Section: Autism and Specific Dietsmentioning
confidence: 98%